The professional image of a nurse as seen by parents of children hospitalized in the oncology department - Wańkowicz, Agnieszka; Bednarek, Anna; Golubka, Ivan; Golubka, Kristiana; Wańkowicz, Piotr; Mierzyński, Radzisław; Golubka, Wiktoria; Dłuski, Dominik; Golubka, Paweł; Darmochwał-Kolarz, Dorota (Polish Journal of Public Health, 2016)
Introduction. The professional image of a nurse which is influenced by a whole variety of factors is the main subject of this work. The social attitudes toward nurses are related to people’s own beliefs, opinions, stereotypes, as well as the nurses’ professional, personal and interpersonal skills. The proper image of a nurse is very important. Patients are becoming increasingly demanding toward nurses which poses new challenges for nurses attempting at creating a positive image of this profession. Aim. The aim of this work was to elicit the opinions about nurses’ work from parents of children hospitalized on the oncologic ward. Material and methods. The authors used a questionnaire of their own making and conducted a literature analysis. The literature review was made using the data taken from Main Medical Library. The research group consisted of 50 parents of children hospitalized in Oncology, Hematology and Child Transplantology Department in Lublin. All the parents were advised about the aim of the study and informed that the questionnaire is anonymous and voluntary. The obtained results have then undergone a statistical analysis, using a Chi2 test. Statistical significance was reached at the level of p<0.05. Results. The most important factors affecting the professional image of a nurse are as follows: the parent’s sex, their place of residence, nurse’s appearance, as well as the following traits: being nice, protective and friendly. Discussion. The image of a nurse as someone who is smiling, friendly and calm appears to be the closest to an ideal picture of such a professional. This pertains not only to parents but to the society as a whole. The nurse should pay attention to patients’ physical needs and expectations, as well as their spiritual side. Conclusions. The researched group provided a positive opinion about the work of nurses at the Department. They paid special attention to their being nice, protective and friendly. It is the nurses’ physical appearance that sheds a positive light on them, as competent and friendly professionals. Even though most people perceive nursing as a rather unattractive profession, there is a huge deal of respect for nurses.